Humanization in caring for patients with chronic-degenerative diseases - Justini Fowler, Danielle; de Sá, Ana Cristina (O Mundo da Saúde, 2009)
Chronic-degenerative diseases are gradual diseases that affect the quality of life of sick people. In view of this aspect and the goal of humanization of relationships and care of people as concerns of health professionals and carers, this study aims to dispel doubts so that one can rethink the ethical relations and values in the process of taking care. Beyond technical-scientific efficiency, there are also ways for practicing sensitivity and solidarity regarding human beings.